Baicalein reduces the invasion of glioma cells via reducing the activity of p38 signaling pathway. - Zhenni Zhang; Jianrui Lv; Xiaoming Lei; Siyuan Li; Yong Zhang; Lihua Meng; Rongliang Xue; Zongfang Li (PLoS ONE)
Baicalein, one of the major flavonids in Scutellaria baicalensis, has historically been used in anti-inflammatory and anti-cancer therapies. However, the anti-metastatic effect and related mechanism(s) in glioma are still unclear. In this study, we thus utilized glioma cell lines U87MG and U251MG to explore the effect of baicalein. We found that administration of baicalein significantly inhibited migration and invasion of glioma cells. In addition, after treating with baicalein for 24 h, there was a decrease in the levels of matrix metalloproteinase-2 (MMP-2) and MMP-9 expression as well as proteinase activity in glioma cells. Conversely, the expression of tissue inhibitor of metalloproteinase-1 (TIMP-1) and TIMP-2 was increased in a dose-dependent manner. Moreover, baicalein treatment significantly decreased the phosphorylated level of p38, but not ERK1/2, JNK1/2 and PI3K/Akt. Combined treatment with a p38 inhibitor (SB203580) and baicalein resulted in the synergistic reduction of MMP-2 and MMP-9 expression and then increase of TIMP-1 and TIMP-2 expression; and the invasive capabilities of U87MG cells were also inhibited. However, p38 chemical activator (anisomycin) could block these effects produced by baicalein, suggesting baicalein directly downregulate the p38 signaling pathway. In conclusion, baicalein inhibits glioma cells invasion and metastasis by reducing cell motility and migration via suppression of p38 signaling pathway, suggesting that baicalein is a potential therapeutic agent for glioma.